1997
DOI: 10.1021/es960655t
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Trichloroethene Desorption from Long-Term Contaminated Soil Using Triton X-100 and pH Increases

Abstract: Laboratory batch and column experiments were conducted to study the effect of relatively low concentrations of Triton X-100 and pH increases on trichloroethene (TCE) desorption from field-contaminated soil to water. TCE desorption from the contaminated soil could not be described by a model that assumes a localized equilibrium between the aqueous- and sorbed-phase concentrations of TCE. A kinetic desorption model, the multi-site model with a γ-distribution of rate constants, was used to interpret the data and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 31 publications
1
42
0
Order By: Relevance
“…Here the adsorption of a low-polarity solute on soil mineral matter is relatively insignificant because of the strong adsorptive competition of water (17). By contrast, unlike ordinary low-polarity solutes, many surfactants (e.g., nonionic and cationic ones) may adsorb efficiently onto certain soil minerals (13)(14)(15), due supposedly to their high polarities and large molecular weights. Surfactants may also partition into SOM, the extent being related to the properties of surfactant and SOM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here the adsorption of a low-polarity solute on soil mineral matter is relatively insignificant because of the strong adsorptive competition of water (17). By contrast, unlike ordinary low-polarity solutes, many surfactants (e.g., nonionic and cationic ones) may adsorb efficiently onto certain soil minerals (13)(14)(15), due supposedly to their high polarities and large molecular weights. Surfactants may also partition into SOM, the extent being related to the properties of surfactant and SOM.…”
Section: Introductionmentioning
confidence: 99%
“…Although this condition can be met by applying very large quantities of surfactant to the system (i.e., X CMC) (13,14), it is desirable to explore conditions for effective soil/solid remediation by use of reduced surfactant loads. In studies of contaminant desorption from soil, it has been shown that low to moderate levels of some surfactants can significantly increase the rate of desorption by increasing the mass-transfer coefficients of contaminants (14,15,(20)(21)(22). In such studies, it is equally important to elucidate the effect of the added surfactant on the contaminant distribution coefficient between soil and water as it would also affect the rate of desorption by changing the contaminant concentration gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, surfactantś can increase desorption rate constants of contaminants, presumably by inducing swelling Ž . of the soil organic matter Sahoo and Smith, 1997;Noordman et al, 1998 . To allow a prediction of the surfactant-enhanced transport of adsorbed contaminants, a more Ž .…”
Section: žmentioning
confidence: 99%
“…Zhu et al (2003) attributed the change in HOCs' distribution coefficients on the surfactantmodified solids to the different structures between the sorbed surfactant thin film and bulk-like medium. Laboratory and in situ studies have been carried out to assess the usefulness of surfactants in remediating soils and aquifers that have been polluted by HOCs; mainly monocyclic and polycyclic aromatic hydrocarbons, chlorinated hydrocarbons (West and Harwell 1992;Sahoo and Smith 1997;Pascoe et al 1998). Similar investigations have been conducted with organic pesticides (Brixie and Boyd 1994;Hermosin et al 1998;Nir et al 2000;Carrizosa et al 2000).…”
Section: Introductionmentioning
confidence: 99%